EFEKTIFITAS MEDIA BOOKLET TERHADAP PENGETAHUAN DAN SIKAP AKSEPTOR TENTANG KONTRASEPSI IUD DI WILAYAH KERJA UPTD PUSKESMAS TABUKAN TAHUN 2025 - Permatasari, Yuliani; Suhrawardi, Suhrawardi; Hipni, Rubiati; Rapidah, Rapidah (Seroja Husada: Jurnal Kesehatan Masyarakat, 2025)
Background: The low level of knowledge and attitude among contraceptive acceptors regarding IUD use is one of the barriers to its utilization. Booklet media, as an educational tool, is expected to enhance knowledge and foster a positive attitude toward IUD contraception. Objective: To determine the effectiveness of booklet media in improving the knowledge and attitudes of contraceptive acceptors toward IUD contraception in the working area of UPTD Puskesmas Tabukan in 2025. Methods: This study employed a quantitative approach with a quasi-experimental design using a pretest-posttest non-equivalent control group. A total of 60 contraceptive acceptors were selected using simple random sampling and divided into two groups: booklet and flipchart (each with 30 respondents). Data were analyzed univariately and bivariately using the Paired T-Test (p < 0.05). Results: The mean knowledge score increased from 47.29 before the intervention to 75.30 after the booklet was given. The attitude score increased from 50.20 to 74.80. The Paired T-Test showed a significant improvement in both knowledge (p = 0.000) and attitude (p = 0.000) after the intervention (p < 0.05). Conclusion: Booklet media is effective in improving knowledge and fostering a positive attitude among contraceptive acceptors toward IUD contraception.